BEZPEČNOSTNÉ ASPEKTY PRI VÝROBE DOPRAVNÝCH PROSTRIEDKOV (Perner's Contacts, 2007)
The paper presents solution of logistic material flows in specific manufacturing environment with use of progressive welding technologies. By using this means we have to observe safety and protection of health at work.
Keywords: logistic; technology; material flows